(untitled) (Research, Society and Development, 2021)
Leprosy is a comorbidity that affects numerous people all over the world, which is characterized by its affinity for the skin and peripheral nerves. The objective of this research was to carry out an analysis of the epidemiological aspects and temporal trends of leprosy indicators in the municipality of Crato. To achieve these objectives, a qualitative and quantitative research was carried out, based on data from the Notifiable Diseases Information System. Between 2007 and 2017, 477 new cases of leprosy were reported in the municipality of Crato, highlighting the year 2012 with the highest number of new cases of the disease, with emphasis on the incidence of cases in men (59.1%), while in women it was 40.8%. Of these, with a predominance of the age group between 50 to 59 years (20.7%), followed by 60 to 69 years (18.6%). According to the results proposed by this research, it can be observed that, in the last few years, there has been a significant reduction in the number of cases. To maintain this index, political commitment and quality health services for effect the service of secondary care in the municipality.